The effects of regular exercise on the number of osteoclasts in ovariectomized Sprague dawley rat mandible - Rini Maya Puspita (Biomedical Engineering, 2015)
Objective: This study aimed to examine the effect of regular exercise on the number of osteoclasts inovariectomized Sprague Dawley rat mandible.Methods: Eight female Sprague Dawley rats, 3 months of age, were ovariectomized and divided into control(untreated) and treatment group (regular exercise). The exercise conducted by the rats ran on a speciallydesigned rat treadmill for 12 weeks, 5 times per week, at a speed of 10-18 m/min for 60 minutes per day. At theend of the treatment, the mandible was taken and cleaned out from the tissue for making the histologicalpreparations with Hematoxylin and Eosin (HE) stain. The number of osteoclasts counted from each histologicalpreparation on 10 visual fields and the obtained data were analyzed using independent t-test.Result: The number of osteoclast was lower significantly in ovariectmized rats compared to control group (P <0.001).Conclusion: Regular exercise can decrease the number of osteoclasts in ovariectomized Sprague Dawley ratmandibles.